Beyond Open Access: Conceptualizing Open Science for Knowledge Co-creation - Mačiulienė, Monika (Frontiers in Communication, 2022)
Despite the calls from European Union and global institutions such as UNESCO and OECD for more openness and co-creation between Quadruple Helix actors (government, academia, industry and civil society), in practice, scientific knowledge creation has been much more closed and fragmented. As an emerging field of study, open science for knowledge co-creation currently requires significant conceptual and theoretical challenges to be addressed before advancing to practical application. To address this gap, the paper aims to develop a conceptual framework integrating diverse understandings of Open Science beyond the use of Open Access and Data practices. We argue that Open Science should be approached as a complex ecosystem with potential for knowledge co-creation and social innovations. The underlying premise of the proposed conceptual model is the interdisciplinarity in integrating multiple reference disciplines. Such an approach allows us to learn from other disciplines and contribute to Open Science research through the emergence of new ideas for theory and practical application.